Scientific Knowledge and Philosophic Thought - Himsworth, Harold (Johns Hopkins University Press, 2019)
Originally published in 1986. Are there two kinds of problems-the scientific and the philosophic-each requiring different methods for solution? Or are there, rather, two different ways of approaching a problem, each yielding a different answer according to the method used? Biomedical researcher Sir Harold Himsworth urges scientists not to shy away from using scientific methods to grapple with problems traditionally accepted as belonging to the province of philosophy. The difference between science and philosophy lies not in the problems to which they are directed, Himsworth argues, but rather in the methods they use for solving them. To the scientist, a proposition is something to be investigated; to the philosopher, something to be accepted as a basis for thought. Since the development of the scientific method, substantial progress has been made toward mastering problems in the natural environment. If we are ever to attain a degree of control over problems that derive from human activities, Himsworth claims that we only succeed by approaching them in a comparably objective way.